20 Years of Scientific Study on Business Intelligence and Decision-Making Performance: A Bibliometric Analysis - Abdessamad Charkaoui; Siham Jabraoui (Journal of Information Systems Engineering and Business Intelligence)
Background: Business intelligence (BI) is an area in which data analytics is applied to generate crucial information supporting business decision-making and has been a significant domain for over three decades. However, there is uncertainty regarding whether investments can effectively improve organizational outcomes.